The effect of pressure on thermal properties of poly(phenacylmethacrylate) - Soykan, C; Sahingoz, R; Yakuphanoğlu, Fahrettin (Springer, 2005)
The influence of pressure on the polyphenacylmethacrylate [poly(PAMA)] was investigated using thermal and scanning electron microscopical (SEM) methods. It is observed that the application of pressure reduces 10% of the initial glass transition temperature. A part from each of the sample was taken for thermogravimetric analysis (TG) and differential scanning calorimetry (DSC). The activation energies were calculated by Ozawa method and significant changing was observed due to this calculation justified the effect of applying pressure.
Keywords: activation energy; pressure effect; thermal analysis